Mathematical modeling of geomorphological risk analysis: a case study of Rocinha/RJ - Brazil - Kunz, Maurício; Luz, Bruno Macali da; Neckel, Alcindo; Faustinoni, Luciano (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2016)
Increasingly interference of human occupation in the environment are connected with the occurrences of natural disasters in hazardous areas. The lack of urban planning, along with human occupation in improper uneven areas for residential purposes, the removal of vegetation and the lack of government control are aspects that are part of the root of this problem affecting the population especially in periods that elevate the rainfall levels. By removing vegetation such areas, the soil becomes more susceptible to water ingress which destabilizes the most part of the soil surface, resulting in undermining. This research has the general objective to demonstrate that, through the use of geo possible to identify risk areas of Rocinha (RJ-Brazil), suggesting possible preventions for future disaster. Thus, to allow the execution of preventive measures. The geoprocessing tools, the collection and analysis of geographic information facilitate the process of decision-making from the information on the areas analyzed, which can serve as a basis for various research studies.